Knowledge and attitude toward elder abuse among adult attendees at Hospital Universiti Sains Malaysia (USM) - Zakaria, Ainul Mardhiah (Universiti Sains Malaysia, 2024)
Elder abuse defined as an act that hurts or upsets an elderly person, either once or often, or by failing to take proper action in any relationship where trust is expected (World Health Organization, 2022). This study aimed to assess the level of knowledge and attitudes towards elder abuse among adult attendees at Hospital Universiti Sains Malaysia (USM). The research, conducted using a cross-sectional design, involved 99 respondents and utilized the Theory of Planned Behaviour as the study framework. The questionnaire used on this study was a self-administered questionnaire that was adopted from Almakki et al. (2020). Data collected were statistically analysed using the SPSS software version 27.0. Pearson Chi Square test was used for data analysis. Results indicated a high level of knowledge 62 (62.6%) among participants regarding elder abuse. Additionally, the level of attitude towards elder abuse among adult attendees at Hospital Universiti Sains Malaysia (USM) was predominantly negative, with 77 (77.8%) of respondents exhibiting a negative attitude, 18 (18.2%) showing a neutral attitude, and only 4 (4.0%) displaying a positive attitude. There is no association between the level of attitude with age, gender, educational status, and type of family toward elder abuse (p = 0.741), (p = 0.167), (p = 0.962), and (p = 0.122) respectively. The study highlights the importance of promoting awareness and understanding of elder abuse to prevent and effectively address cases within the community.